The state of systematics of North American Baetis Leach, 1815 (Ephemeroptera: Baetidae), with recommendations for identification of larvae - Webb, J.m.; Jacobus, Luke M.; Sullivan, S.p. (Zootaxa, 2018)
The North American species of Baetis Leach (Ephemeroptera: Baetidae) are reviewed. Nearly one-third of species are either unknown or inadequately described in the larval stage, a fact not reflected in most keys or standard taxonomic efforts for bioassessment, which typically recommend species-level identifications of larvae. Furthermore, our new observations indicate that some previously published stage associations should be viewed as only tentative, and molecular evidence suggests that current species taxonomy does not reflect biological species. In order to acknowledge these deficiencies, but at the same time provide a degree of higher taxonomic resolution beyond the genus level, we recommend a scheme for identifications incorporating previously established species groups and the species complexes and species included within them. Species complexes are proposed for instances when there are either multiple species that cannot be differentiated in the larval stage or when multiple lines of evidence indicate more than one actual species is included in a single species concept. Complexes include B. flavistriga complex (B. flavistriga McDunnough + B. phoebus McDunnough + B. rusticans McDunnough), B. intercalaris complex (B. intercalaris McDunnough), B. vernus complex (B. brunneicolor McDunnough + B. vernus Curtis), B. bicaudatus complex (B. bicaudatus Dodds), B. tricaudatus complex (B. tricaudatus Dodds), and B. piscatoris complex (B. piscatoris Traver + B. palisadi Mayo + B. persecutus McDunnough [=B. persecutor McCafferty n. obj. syn]). A new larval identification key incorporating the B. piscatoris complex is provided.